2013
DOI: 10.1016/j.tjog.2012.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Two-year neurological outcome of very-low-birth-weight children with prenatal absent or reversed end-diastolic flow velocity in the umbilical artery

Abstract: VLBW children delivered earlier than 29 gestational weeks with abnormal umbilical blood flow velocity prenatally have greater mental developmental delay at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…We found that UA blood flow was better in NWMAA. Pathological UA blood flow relates to adverse outcome and neurological sequels [ 28 ]. Normal UA blood flow is almost never connected with adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on pathological antenatal Doppler flow used less robust matching criteria with an increased UA resistance index >95 percentile instead of UA AREDF (8; 33) or smaller sample sizes with UA AREDF30 34 35 or included no control group,33 but showed also that pathological antenatal Doppler flow is associated with unfavourable cognitive outcome, but not with motor development in former VLBW infants at 2 years of age 33 34. Another study that compared only 16 very preterm infants with UA AREDF to GA-matched eutrophic controls found higher rates of mental delay and a tendency to more frequent motor problems at age 2 years, which was not surprising 35.…”
Section: Discussionmentioning
confidence: 99%